2018
DOI: 10.1007/s00586-018-5849-9
|View full text |Cite
|
Sign up to set email alerts
|

Intrasubject repeatability of in vivo intervertebral motion parameters using quantitative fluoroscopy

Abstract: Purpose In vivo quantification of intervertebral motion through imaging has progressed to a point where biomarkers for low back pain are emerging. This makes possible deeper study of the condition's biometrics. However, the measurement of change over time involves error. The purpose of this prospective investigation is to determine the intrasubject repeatability of six in vivo intervertebral motion parameters using quantitative fluoroscopy. Methods Intrasubject reliability (ICC) and minimal detectable change (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 43 publications
3
39
0
Order By: Relevance
“…However, the QF protocols are, by definition, quantitative and in this study resulted in effective radiation dosages of less than 0.3 mSv each. This is considerably less than the 1.3 mSv quoted as the typical effective dose expected for a series of X-rays of the lumbar spine for diagnostic purposes 33,34 . This makes continued of the use of plain radiographs difficult to justify for most cases where degrees of increased translation that are not measurable might be acted upon.…”
Section: Discussionmentioning
confidence: 74%
“…However, the QF protocols are, by definition, quantitative and in this study resulted in effective radiation dosages of less than 0.3 mSv each. This is considerably less than the 1.3 mSv quoted as the typical effective dose expected for a series of X-rays of the lumbar spine for diagnostic purposes 33,34 . This makes continued of the use of plain radiographs difficult to justify for most cases where degrees of increased translation that are not measurable might be acted upon.…”
Section: Discussionmentioning
confidence: 74%
“…Two sources of systematic and random error in QF that may affect the measurements of intervertebral motion sharing are trial-to-trial variability within a subject (intrasubject variability) and error from investigator input (intra- and inter-investigator variability). A recent study established intrasubject reliability for MSI and MSV in passive recumbent and active weight-bearing lumbar spine flexion, extension, and lateral bending and another study determined the machine error for single level motion [ 10 , 11 ]. Other previous work in passive recumbent flexion reported intrasubject reliability (which includes instrument error) as substantial for MSI (ICC 0.61, 95% CI 0.34–0.78) and moderate for MSV (ICC 0.41, 95% CI 0.00–0.66).…”
Section: Discussionmentioning
confidence: 99%
“…Error from repeated measures of a subject reflecting their trial-to-trial variability were not taken into account. Although a previous study established intrasubject repeatability [ 10 ], determining the relative contribution of error associated with investigator input and error associated with the subject’s variability to the total measurement error remains a challenge. Future studies should evaluate other sources of error that may occur during QF image acquisition and analysis (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar concepts of maximum motion have been documented as repeatable. Breen et al demonstrated substantial to excellent reliability of repeated measurements of intervertebral range of angular joint motion in low back joint motion analysis, measured under video uoroscopy (16). Consequently, it can be theorised that repeated measurements of intervertebral range of motion in the cervical spine are similarly reliable.…”
Section: Introductionmentioning
confidence: 99%